An In vitro comparative evaluation of effect of novel irrigant Qmix and 17% ethylenediaminetetraacetic acid on the push-out bond strength of biodentine and endosequence bioceramic root repair material - Vandana J Gade; Aparajita Gangrade; Jaykumar R Gade; Neelam Rahul (Wolters Kluwer Medknow Publications, 2021)
Background: Perforations can occur during any endodontic procedure which may affect prognosis if not repaired immediately. During perforation repair, various irrigating solutions were used which may affect the bond strength of repair materials. Methods: In this study, sixty dentin slices of 2 mm thickness were prepared with lumen 1.3 mm. Samples were divided into two groups. Biodentine and EndoSequence Root Repair Material (RRM) were placed in the respective samples and incubated for 24 h. Subdivision of groups into three was done: control, 17% ethylenediaminetetraacetic acid (EDTA), and QMix. Immersion was done for 30 min, followed by incubation for 48 h. The samples were then tested for compressive strength through a push-out test. The mean, standard deviation, median, and range of bond strength of EndoSequence Bioceramic RRM and Biodentine were obtained. One-way analysis of variance was used to determine the statistical significance of difference in the mean push-out strengths of each material across decalcifying agents. Paired analysis of push-out strength between decalcifying agents for each material was performed using Tukey's post hoc test. All the analyses were performed using R-3.0.0 programming language, and the statistical confidence was tested at 95%. Results: Results showed that EndoSequence RRM had superior bond strength than Biodentine. 17% EDTA and QMix showed negative influence on the bond strength. However, QMix samples had more bond strength than 17% EDTA. Conclusion: QMix showed less negative influence than EDTA on Biodentine and EndoSequence RRM.